Comprehensive risk score of the E-PASS as a prognostic indicator for patients after elective and emergency curative colorectal cancer surgery: A multicenter retrospective study. (May 2022) - Kato, Yujin; Shigeta, Kohei; Tajima, Yuki; Kikuchi, Hiroto; Hirata, Akira; Nakadai, Jumpei; Sugiura, Kiyoaki; Seo, Yuki; Kondo, Takayuki; Okui, Jun; Matsui, Shimpei; Seishima, Ryo; et al.
Abstract: Objective: To evaluate the prognostic value of the comprehensive risk score (CRS) of the Estimation of Physiologic Ability and Surgical Stress for managing patients with colorectal cancer (CRC) who underwent elective and emergency colorectal cancer surgery with curative intent. Summary background data: CRS, which is calculated based on both clinical and surgical factors, is a good predictor of postoperative complications and mortality. However, the impact of CRS in CRC prognosis remains unclear. Methods: Patients with CRC who underwent curative resection between 2010 and 2019 were retrospectively enrolled in this study. The cohort was divided into the low and high CRS groups. The prognostic value of CRS was evaluated via Cox regression and Kaplan–Meier analyses. The CRS cutoff value was obtained using the Youden index applied to OS curves and have not been validated by any validation cohorts. Results: In total, 2407 patients, including 1359 and 1048 patients with low and high CRS, respectively, were enrolled in this study. Multivariate analysis revealed that a CRS was an independent prognostic factor of overall and recurrence-free survival regardless of disease stage. Furthermore, adjuvant chemotherapy was beneficial for the survival of patients with stage III CRC in both high and low CRS groups; however, the survival benefit was limited in elderly high CRS patients. Conclusions: CRS was a strong prognostic factor for CRC regardless of disease stage and might be considered as a biomarker for selecting elderly patients who are eligible for adjuvant chemotherapy. Highlights: Comprehensive Risk Score (CRS) of E-PASS is a strong prognostic factor for colorectal cancer. High CRS group has poor prognostic outcome. Adjuvant chemotherapy has limited benefits for elderly patients with a high CRS.